Exploring the Molecular Basis of Antifungal Synergies Using Genome-Wide Approaches - Agarwal, Ameeta; Tripathi, Siddharth; Xu, Tao; Jacob, Melissa; Li, Xing-Cong; Clark, Alice (Frontiers in Microbiology, 2012)
Drug resistance poses a significant challenge in antifungal therapy since resistance has been found for all known classes of antifungal drugs. The discovery of compounds that can act synergistically with antifungal drugs is an important strategy to overcome resistance. For such combination therapies to be effective, it is critical to understand the molecular basis for the synergism by examining the cellular effects exerted by the combined drugs. Genomic profiling technologies developed in the model yeast Saccharomyces cerevisiae have been successfully used to investigate antifungal combinations. This review discusses how these technologies have been used not only to identify synergistic mechanisms but also to predict drug synergies. It also discusses how genome-wide genetic interaction studies have been combined with drug-target information to differentiate between antifungal drug synergies that are target-specific versus those that are non-specific. The investigation of the mechanism of action of antifungal synergies will undoubtedly advance the development of optimal and safe combination therapies for the treatment of drug-resistant fungal infections.